Foot Self Care Education To Prevent Diabetic Ulcers: Edukasi Foot Self Care Untuk Mencegah Ulkus Diabetik - Nistiandani, Ana; Widayati, Nur (Al-Hijrah Indonesia, 2022)
The major complication of diabetes mellitus that needs special attention at this time is diabetic ulcers. Diabetic ulcers on the feet can reduce the quality of life and cause death. A lack of knowledge about foot care can cause this. In addition to controlling blood sugar levels, people with diabetes need education about foot care that is applied independently at home (foot self-care). This service aims to enable participants to understand and implement foot self-care to prevent diabetic ulcers. The educational method is given by lecture. Community service activities are carried out in four stages: education, discussion, question and answer, and evaluation. Participation partners involved are the Gucialit village community, totaling 25 people. Characteristics of the participants indicated that the gender of the majority of participants was male, totaling 17 people (68%), dominated by late adulthood, totaling 15 people (60%), and the majority were farmers, totaling 22 people (88%). The service results show increased knowledge about foot self-care to prevent diabetic ulcers before and after being given education. Further education on foot self-care can be given using a simulation method so that people can practice it directly.